Baja Oklahoma - Jenkins, Dan (Book collections on Project MUSE., 2010)
Dan Jenkins' second best-known novel, Baja Oklahoma, features protagonist Juanita Hutchins, who can cuss and politically commentate with the best of Jenkins' male protagonists. Still convincingly female, though in no way dumb and girly, fortyish Juanita serves drinks to the colorful crew patronizing Herb's Cafe in South Fort Worth, dates a fellow middle-ager whose connections with the oil industry are limited to dipstick duty at his filling station, and also hopes to become a singer-songwriter in the real country tradition of Bob Wills and Willie Nelson. Too many of her early songwriting resu.